2012
DOI: 10.1021/jf300861c
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Phenolic Compounds from Color and Flavor Problems to Health Benefits

Abstract: Early studies focused on the negative effects on color and flavor of foods, followed by exploration of the antioxidant properties and the associated health benefits. The growing body of evidence suggests that plant-based polyphenols may help prevent or delay the onset of a multiplicity of diseases. Newer work suggests that a variety of polyphenols can alter the expression of genes in the inflammatory pathway. Data also show that the absorption of the polyphenols is very limited. Insulin resistance and endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
128
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(135 citation statements)
references
References 247 publications
0
128
0
7
Order By: Relevance
“…Previous studies have shown that the mean dietary intake of total phenolic compounds is 780 mg per day for females and 1058 mg per day for males, with half of these composed of hydroxycinnamates, 20−25% of total flavonoids, and approximately 1% of anthocyanins [28]. These requirements can be achieved with the intake of portions of aproximately 50 g of P. spinosa and 150 g of C. monogyna fruits (edible part).…”
Section: Identification Of Phenolic Compounds Of the Fruitsmentioning
confidence: 99%
“…Previous studies have shown that the mean dietary intake of total phenolic compounds is 780 mg per day for females and 1058 mg per day for males, with half of these composed of hydroxycinnamates, 20−25% of total flavonoids, and approximately 1% of anthocyanins [28]. These requirements can be achieved with the intake of portions of aproximately 50 g of P. spinosa and 150 g of C. monogyna fruits (edible part).…”
Section: Identification Of Phenolic Compounds Of the Fruitsmentioning
confidence: 99%
“…Such highly desirable 'one-pot' catalytic cascades therefore necessitate the spatial separation of each catalytic step. The catalytic advantage of spatially segregating Pt NPs within mesopores, accessible overwhelmingly only through interconnected macropores containing Pd NPs, was explored for the cascade oxidative dehydrogenation of cinnamyl alcohol  cinnamaldehyde  cinnamic acid, the latter an important flavorant and essential oil 21,22 . Pd is highly selective for catalyzing cinnamyl alcohol oxidation to cinnamaldehyde 23,24 , but promotes decarbonylation of the resultant aldehyde product; in contrast, Pt favours undesired hydrogenation of cinnamyl alcohol (via reactively-formed surface hydrogen) to 3-phenylpropionaldehyde 25 , but is highly selective towards cinnamaldehyde oxidation to the desirable cinnamic acid product 26 .…”
mentioning
confidence: 99%
“…Flavonoids and polyphenolic acids are the most abundant compounds in tea leaves and extracts and they are primarily responsible for the beneficial healthful properties of tea [4,5]. Antioxidative properties of phenolic compounds are manifested particularly by their abilities to inhibit free radical generation, scavenge free radicals, and chelate transition metal ions, mainly iron and copper, which are catalysts of free radical reactions [6,7]. They also prevent free radical generation by inhibiting activity of existing enzymes or by increasing the activity of enzymes with antioxidative properties, probably on the way of induction of protein molecule biosynthesis [8,9].…”
Section: Abstract: Black Tea; Antioxidant Properties; Flavonoidsmentioning
confidence: 99%